Limitations of Using Mobile Phones for Managing Type 1 Diabetes (T1D) Among Youth in Low and Middle-Income Countries: Implications for mHealth - Wyche, Susan; Olson, Jennifer; Karanu, Mary; Omondi, Eric; Olonyo, Mike (Proceedings of the ACM on human-computer interaction, 2024)
The prevalence of Type 1 Diabetes (T1D) among youth is increasing worldwide. Mobile phones, particularly mHealth applications, can potentially improve youth's management of this chronic condition. However, the design of these services rarely accounts for users in low and middle-income countries (LMICs). In this paper, we investigate factors that influence the use of mobile phones for managing T1D among youth in rural and urban Kenya. Our analysis draws from 58 interviews conducted with T1D youth (between the ages of 11 and 18 years old), their caregivers, and other significant stakeholders, including doctors and schoolteachers. Our findings draw attention to a significant mismatch between the mobile phone features prioritized in mHealth apps and participants' usage practices. We discuss the practical implications of these findings for mHealth design and user research.